Teori situasi publik (STP): mengungkai isu komunikasi whatsapp di malaysia - Shafie, Siti Azura; Hashim, Norliana (Penerbit UKM, 2023)
WhatsApp communication issues often occur in any government or private organization. The problem of WhatsApp communication that employers give work instructions outside working hours has caused work stress to employees. Drawing form, the communication perspectives, this study applies Situational Theory of Public (STP) to identify the perception of the situation and communication behaviors formed among employees of Universiti Putra Malaysia (UPM). The specific objective of this study is to identify the perceptions and communication behaviors of employees in problem situations when employers give work instructions outside of working hours via WhatsApp. This information can influence the way individuals engage in search activities, selection, and information processing as a step to the problem-solving process from the point of view of WhatsApp communication at UPM. This study also examined the relationship between situational perceptions and communication behaviors. This study used a questionnaire as an instrument. The sample (N=364) comprising UPM employees have responded to this study. The result showed that significantly the identification of constraints recognition among UPM employees is the most important predictor variable in communication behavior (ß = .109, p <.05) and contributed a variance of 34%. The involvement recognition the major second predictor that contributed in communication behavior was (β = .30, p <.05) with a variance contribution of 33%. Next, problem recognition (β = .32, p <.05) with a variance contribution of 26% is a predictor that less contributes to communication behavior. A critical discussion of WhatsApp communication problem solving is able to provide significant conclusions to the organization to frame more effective communication.